Optimizing School Financial Management with Activity-Based Costing : Case Study at Parlaungan Islamic Middle School - Lis Setyowati (Jurnal Ekonomi Manajemen Akuntansi, 2024)
The business world is currently experiencing very rapid growth, both in manufacturing and services. One form of service business is educational institutions. Educational institutions that are common in society are schools. Schools must be able to provide good-quality facilities so as to produce quality human resources for the next generation.. This research aims to purpose of this research is to calculate the tuition fees of Parlaungan Islamic Middle School.. The research method used is A qualitative method, descriptive analysis describes the method of determining the SPP rates of Parlaungan Islamic Middle School, which has been applied in the school so far using the Activity Based Costing (ABC) method.. From the results of observations that have been made, it can be seen that in determining the SPP rate, the basis for calculation is the Salary of Teachers and Employees. The results of this study indicate that the calculation of the SPP rate of SMP Islam Parlaungan has used the Activity Costing (ABC) method, but in determining the rate results, the school rounds down. This is to make the cost allocation more efficient. The SPP rate determined by the school management is IDR 65,000, but based on calculations using the Activity Based Costing (ABC) method, the SPP rate is IDR 65,909 (rounded up) to IDR 66,000. This causes undercost.